A Five Years Retrospective Study of Incidental Findings in Medico-Legal Autopsies - Raihan Uddin Ahmed1 , Nitu Kumar Gogoi2 , Nabajit Barman3 , Diganta Thakuria4 , Pradeep Kumar Thakur (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim of the study: The aim of the study is to find out the spectrum of incidental pathological lesions inthe deceased during medico legal autopsy which are not directly related to the cause of death. This studyemphasizes the incidence of various incidental lesions which otherwise would have been unnoticed duringa person’s life.Materials and method: A five years retrospective study was conducted from 2012 to 2017 at the departmentof Forensic medicine Assam Medical College and hospital,. The organs where the pathological lesions weredetected mostly comprise of lungs, liver, kidneys and heart. The sections from organs were preserved in10% formalin and prepared for histopathological examination. The gross and histopathological findingswere noted.Results: 75 cases of cirrhosis of liver, 62 cases TB lung,93 cases of coronary artery disease and 18 casesof cystic lesions of kidney were detected where the cause of death is not directly related with these lesions.